ESTIMATION OF HETEROSIS FOR EARLINESS AND YIELD CONTRIBUTING TRAITS IN CUCUMBER ( CONTRIBUTING TRAITS IN CUCUMBER (Cucumis sativus Cucumis sativus L.) - MANISHA THAKUR,; AND SANDEEP KUMAR, RAMESH KUMAR (The Bioscan, 2018)
The research was conducted at Experimental Research Farm of the Department of Vegetable Science, Dr YS Parmar University of Horticulture and Forestry, Nauni, Solan, HP during 2015-2016 to estimate the heterosis for earliness and yield contributing traits. Six genotypes were used to develop 15 F1 hybrids of cucumber by half diallel mating design. The mean sum of squares were highly significant for all the characters indicated a wide genetic variation for the characters studied and there is a possibility of genetic improvement using such genetic pools in future breeding programme.The genotypes P1-618860, UHF-CUC-1, UHF-CUC-2 and Khira-75 were found superior on the basis of mean performance for earliness and yield related characters. Appreciable heterosis was observed over better parent and standard check for most of the characters studied. The F1 hybrids those found to be superior in performance over better parent and standard check for various characters under study were Khira-75 x PI-618860 (16.30 & 65.71), Khira-75 x UHF-CUC-2 (23.48 & 60.22) and Khira-75 x UHF-CUC-1 (23.01 & 59.60) including yield per plot and per hectare respectively, can be exploited for commercial cultivation.